Forensic value of nine STR loci in Northern Thai - Tanin Bhoopat (2018)
Nine STR loci (D3S1358, D5S818, D7S820, D8S1179, D13S317, TH01, VWA, TPOX, LPL) were studied in a large Northern Thai population sample. All loci meet Hardy-Weinberg expectations. The combined power of discrimination and exclusion is 0.9999999979 and 0.99798 respectively. Mutation rates for STR loci did not exceed 1-4 per 1000 parent/child pairs as derived from disputed paternity cases. Similar mutation rates were also reported from other populations. No mutations were found for D5S818, D7S820, TH01, and TPOX. © 2005 Elsevier Ireland Ltd. All rights reserved.